If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=y-43/5
We move all terms to the left:
9-(y-43/5)=0
We add all the numbers together, and all the variables
-(+y-43/5)+9=0
We get rid of parentheses
-y+9+43/5=0
We multiply all the terms by the denominator
-y*5+43+9*5=0
We add all the numbers together, and all the variables
-y*5+88=0
Wy multiply elements
-5y+88=0
We move all terms containing y to the left, all other terms to the right
-5y=-88
y=-88/-5
y=17+3/5
| 3/4b=228 | | 39-5x=-26 | | 5(2x-3)=6x-7 | | 4x-9-3=-13 | | 4y-3(y-2)=0 | | 45=n/5+39 | | 5-9(3)=12+6x(2) | | a+15=250 | | 66+8x=154 | | -5(8b+5)=215 | | 72=3x+3=180 | | m/7+16=19 | | t+1/2=11/4 | | 4x-4(-5/8)=-1 | | t-1/2=11/4 | | -4=7+x/4 | | 8(-7x+8)=-106 | | –10m=5m+3(–4m−3) | | 10x–(2x+4)=30 | | 6(y+15)=-18 | | 64=x+50 | | -5(5x-4)=-5x+5 | | 6x-41=-41 | | 2(-5+7k)=-108 | | 54=x12. | | 70=-15+b | | 321y=2409 | | l/90=188/360 | | c/15=5 | | 2(-5+7k)=108 | | x/90=188/360 | | 6y=90y= |